2021
DOI: 10.1002/gj.4263
|View full text |Cite
|
Sign up to set email alerts
|

Facies and bed type characteristics of channel‐lobe transition deposits from the Oligocene‐Miocene Tajau Sandstone Member, Kudat Formation, Sabah, Malaysia

Abstract: Channel‐lobe transition zones (CLTZs) are identified in many modern deep‐water systems, but few exhumed examples have been identified. Exposures of the Oligocene‐Miocene Tajau Sandstone Member (TSM), Kudat Formation, northern Sabah, Malaysia, provides the opportunity to document a CLTZ from an active basin margin. This work provides the first detailed field‐based sedimentological logging to produce a quantitative database on facies, sedimentary structures, bed type, and statistical analysis. This is particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 182 publications
(399 reference statements)
0
8
0
Order By: Relevance
“…The preservation of a thicker stratigraphic record for CLTZs has been explained by high aggradation rates (e.g., Pemberton et al, 2016; Figure 10), tectonically-active settings (Ito, 2008;Mansor and Amir Hassan, 2021;Brooks et al, 2022), rapid abandonment or avulsion of feeder channels before erosion into the CLTZ (e.g., Hofstra et al, 2015;Brooks et al, 2018), or a large-scale passive margin setting allowing more net aggradation (Navarro and Arnott, 2020). Nonetheless, these studies also interpret lobes and channel-fills as part of the stratigraphic succession, which points to an aggrading and interfingering succession where the CLTZ is relatively fixed, and preserved as surfaces and thinner stratigraphic units as part of a thicker succession.…”
Section: Exhumed Thin Cltzs (< 10 M Thick)mentioning
confidence: 99%
See 2 more Smart Citations
“…The preservation of a thicker stratigraphic record for CLTZs has been explained by high aggradation rates (e.g., Pemberton et al, 2016; Figure 10), tectonically-active settings (Ito, 2008;Mansor and Amir Hassan, 2021;Brooks et al, 2022), rapid abandonment or avulsion of feeder channels before erosion into the CLTZ (e.g., Hofstra et al, 2015;Brooks et al, 2018), or a large-scale passive margin setting allowing more net aggradation (Navarro and Arnott, 2020). Nonetheless, these studies also interpret lobes and channel-fills as part of the stratigraphic succession, which points to an aggrading and interfingering succession where the CLTZ is relatively fixed, and preserved as surfaces and thinner stratigraphic units as part of a thicker succession.…”
Section: Exhumed Thin Cltzs (< 10 M Thick)mentioning
confidence: 99%
“…Detailed outcrop research on CLTZs has primarily focused on large, relatively tectonically-quiescent basins associated with mature passive margins or thermal sag basins, and influenced by glacial-interglacial cycles, such as the Karoo Basin in South Africa (e.g., Van der Merwe et al, 2014;Hofstra et al, 2015;Brooks et al, 2018). Therefore, it is important to understand if these same models can be applied to tectonically-active basins (e.g., Mansor and Amir Hassan, 2021;Brooks et al, 2022), such as forearc or retroarc foreland basins, formed in different climatic conditions in both modern environments and in the rock record. Indeed, tectonically-active basin-fills are likely to host CMEZs given the steeper slopes.…”
Section: Future Opportunities For Channel Mouth and Cltz Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid beds develop through flow transformation following significant entrainment of a muddy substrate and/or declining turbulent energy (Amy & Talling, 2006; Haughton et al, 2003, 2009; Hodgson, 2009; Lucchi & Valmori, 1980; Muzzi Magalhaes & Tinterri, 2010; Southern et al, 2015), and are commonly observed within the distal fringes of lobe systems (Fonnesu et al, 2018; Haughton et al, 2003; Hodgson, 2009; Kane & Pontén, 2012; Kane et al, 2017). Recently, studies have shown that hybrid beds can also develop in base‐of‐slope settings (Baas et al, 2021; Brooks et al, 2018a; Fonnesu et al, 2018; Ito, 2008; Mansor & Amir Hassan, 2021), and are generally associated with frontal lobes (Mueller et al, 2017; Spychala et al, 2017a, 2017b, 2021). The stratigraphic distribution of hybrid beds has been linked to the character of the supply slope and seafloor relief, where hybrid beds are invoked to develop during periods of disequilibrium in out‐of‐grade slopes (Haughton et al, 2003, 2009; Hodgson, 2009; Pierce et al, 2018; Spychala et al, 2017a, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, outcrop studies (Brooks et al, 2018a(Brooks et al, , 2018bHofstra et al, 2015;Ito, 2008;Pemberton et al, 2016;Pyles et al, 2014; Van der Merwe et al, 2014) have helped develop recognition criteria for CLTZs, which include: a thin stratigraphic expression; amalgamated erosional features; coarse-grained/mudclast lag deposits; aggradational bedforms (i.e. sediment waves); soft-sediment deformation; interfingering of up-dip and down-dip deposits; and sand-rich hybrid beds in proximal lobes (Brooks et al, 2018a;Mansor & Amir Hassan, 2021;Stevenson et al, 2015). Detailed outcrop research on CLTZs has often focussed on large, relatively tectonically quiescent basins associated with mature passive margins, or thermal sag basins, such as the Karoo Basin in South Africa (Brooks et al, 2018a;Hofstra et al, 2015;Van der Merwe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%